The Effect of Managerial Ability and Tone of Earnings Announcements towards Market Reactions - Zaenal Fanani; Zakiyyah Riris Merbaka (Institute of Research and Community Outreach - Petra Christian University, 2020)
This study aims to examine and analyse the effect of Managerial Ability, Tone of Earnings Announcements, and Market Reactions. Using Return on Asset and Firm Size as control variables. In this study population taken is manufacturing companies that are listed on the Indonesia Stock Exchange during the year 2015-2016. Based on the population criteria set, the sampling method is purposive sampling. The sa